2017
DOI: 10.1021/acs.nanolett.7b01544
|View full text |Cite
|
Sign up to set email alerts
|

Ultrapure Green Light-Emitting Diodes Using Two-Dimensional Formamidinium Perovskites: Achieving Recommendation 2020 Color Coordinates

Abstract: Pure green light-emitting diodes (LEDs) are essential for realizing an ultrawide color gamut in next-generation displays, as is defined by the recommendation (Rec.) 2020 standard. However, because the human eye is more sensitive to the green spectral region, it is not yet possible to achieve an ultrapure green electroluminescence (EL) with a sufficiently narrow bandwidth that covers >95% of the Rec. 2020 standard in the CIE 1931 color space. Here, we demonstrate efficient, ultrapure green EL based on the collo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
211
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(213 citation statements)
references
References 57 publications
2
211
0
Order By: Relevance
“…As a result, the color gamut covers 104% of the Rec. 2020 standard in the CIE 1931 color space, demonstrating the purest green emission ever reported . In terms of the National Television System Committee standard, the color gamut is as high as 123% in the CIE 1931 color space.…”
Section: Summary Of Led Performancesmentioning
confidence: 84%
See 1 more Smart Citation
“…As a result, the color gamut covers 104% of the Rec. 2020 standard in the CIE 1931 color space, demonstrating the purest green emission ever reported . In terms of the National Television System Committee standard, the color gamut is as high as 123% in the CIE 1931 color space.…”
Section: Summary Of Led Performancesmentioning
confidence: 84%
“…For instance, Kumar et al demonstrated a green LED with 2D formamidinium lead bromide hybrid perovskites, achieving a color gamut covering 96.8% of the Rec. 2020 standard in the CIE 1931 color space, which is the “greenest” LED reported thus far . Using supercrystal inorganic perovskites, Tong et al also reported an LED exhibiting a color close to the Rec.…”
Section: Summary Of Led Performancesmentioning
confidence: 99%
“…The characteristics are slightly lower than the bulk perovskite LED devices in which the emission wavelength is difficult to fine tune. We report the operational life time (LT 50 ) at initial luminance of approximately 1000 nits (at 10 mA cm −2 ) to be around 3 hours . Clearly, more work needs to be done to enhance the operational lifetimes in the EL‐based perovskite devices.…”
Section: Led Device Design and Performancementioning
confidence: 95%
“…However, OIHP semiconductor NCs can be easily integrated into optoelectronic devices, including the LEDs . In practice, an important motivation for the development of perovskite LEDs is the need of monochromatic light sources covering the entire visible range, in particular in the deep green spectral region, because the human eyes can distinguish more color tones in the green wavelength region . Assuming fixed blue and red primaries in the CIE color coordinates, Figure presents the calculated coverage of Rec.…”
Section: Structure Synthesis and Rec 2020mentioning
confidence: 99%
“…A precursor solution of methylammonium bromine (MABr) and PbBr 2 with a molar ratio of 3:1 dissolved in dimethylformamide (DMF) was used to deposit luminescent MAPbBr 3 films on the indium tin oxide (ITO) glass substrates with precoated poly(3,4‐ethylenedioxythiophene):polystyre sulfonate (PEDOT:PSS) and poly(9‐vinycarbazole) (PVK) films (glass/ITO/PEDOT:PSS/PVK). A hole transport layer (HTL) such as PVK or poly( N , N ′‐bis(4‐butylphenyl)‐ N , N ′‐bis(phenyl)‐benzidine) (poly‐TPD) was often deposited on PEDOT:PSS for perovskite nanocrystal‐based LEDs to improve the hole injection into luminescent perovskite nanocrystals due to the decreased hole injection energy barrier from the highest occupied molecular orbital level of PEDOT:PSS to the valence band maximum of perovskite nanocrystals. The as‐prepared MAPbBr 3 films were then transferred into humid controllable chamber with a fast postmoisture exposure treatment after annealing in nitrogen glove box.…”
Section: Pl Lifetime and Qy Of The As‐prepared Mapbbr3 Films Exposed mentioning
confidence: 99%